TREATMENT METHODS FOR OBESITY IN ADULTS: ADVANTAGES AND DISADVANTAGES – LITERATURE REVIEW - Dominika Karolak,; Tymoteusz Białowąs,; Natalia Sara Kuśmierowska,; Monika Kuś,; Grzegorz Słomkowski,; Kacper Cholewiński,; Daria Valipur Kolti,; Milena Polak,; Magdalena Natalia Nowak,; Konrad Wiśniewski, (International Journal of Innovative Technologies in Social Science, 2026)
Background: Obesity is a growing public health crisis requiring timely intervention to prevent severe comorbidities (e.g., cardiovascular disease, type 2 diabetes) and improve patient survival.Aim: To evaluate current obesity therapies—lifestyle modifications, pharmacotherapy, bariatric surgery, and experimental methods (FMT, DBS)—comparing their efficacy, complications, and required patient effort.Materials and Methods: A targeted PubMed literature review using keywords such as "obesity treatment" and "bariatric surgery."Results: Obesity has a multifactorial etiology. Lifestyle modifications are foundational but typically yield a modest weight loss of 5-10% and are limited by counter-regulatory mechanisms. Pharmacotherapy (e.g., GLP-1 receptor agonists) provides significant reduction (~20%), whereas bariatric surgery remains the most effective intervention for substantial, sustained weight loss and comorbidity remission.Conclusion: Standalone lifestyle interventions are often insufficient due to high weight regain rates. Optimal long-term clinical outcomes require an individualized, integrated approach combining permanent behavioral changes with appropriate pharmacological or surgical therapies.